PEMBINAAN PENGGUNAAN ALAT PERMAINANAN EDUKATIF UNTUK MEMPERMUDAH PROSES PEMBELAJARAN PADA PERUM GREEN VIEW - Anggia Arista; Rahmat Fauzi; Handra Tipa; Yuliadi (PUAN INDONESIA, 2026)
Developing all aspects of intelligence in early childhood can be achieved in various ways, one of which is through the use of educational teaching aids (ETA). These teaching aids aim to develop different aspects of a child’s development, such as physical-motor skills, cognitive abilities, language, social-emotional skills, art, and moral values. The creation of educational teaching aids can be done conceptually without requiring high costs. They can be made by utilizing recycled or used materials available around the learning environment. Teaching aids created by tutors themselves can be used effectively and efficiently. The use of educational teaching aids can be integrated with appropriate learning methods or models so that all aspects of children’s intelligence can develop optimally. The teaching aids produced include stacking blocks, replicas of letters and numbers, and coding books for matching pictures. Toddlers are able to play and learn well, and the creativity of early childhood learners in the Green View housing complex has increased. This is evidenced by the improvement in early childhood learners’ ability to recognize letters and numbers